"...In Kiambu county, there are different things being done": A qualitative exploration of healthcare workers' experiences with cord care practices. - James Maina Githinji; Angeline Chepchirchir; Brian Ombura Nyanchoka; Prabhjot Kaur Juttla; Ruth Nduati (PLoS ONE)
Introduction Neonatal sepsis (NNS) continues to be a leading cause of neonatal mortality in low-resource settings. NNS can occur secondary to umbilical stump infections (omphalitis) and this requires preventative cord care practices. To address this, the World Health Organization (WHO) issued context-specific recommendations for the use of 7.1% chlorhexidine (CHX) solution in areas with high neonatal mortality. Despite adoption of this policy, monitoring and evaluation of this guidance is lacking. This study describes the experiences of healthcare workers (HCWs) regarding cord care practices in Kiambu County, Kenya. Methods We employed an exploratory qualitative design. Key informant interviews were conducted with 38 HCWs between October 6th and November 9th 2022 in six healthcare facilities in Kiambu County. Data were analyzed thematically using NVivo software. Results While Ministry of Health guidelines endorse WHO's recommendation for the nation-wide use of CHX for neonatal cord care, its implementation in Kiambu county remains varied. HCWs continue to favour surgical spirit, and one of the healthcare facilities in our study adopted a facility-based policy of dry cord care. HCWs also relayed that mothers often combined modern and traditional methods. Some HCWs reported high satisfaction with CHX due to its perceived effectiveness, ease of use, and faster stump healing. However, systemic and product-specific barriers to uptake were noted. Systemic issues included frequent CHX stock-outs and high out-of-pocket costs due to inconsistent county-level supply and lack of insurance coverage. Product-specific concerns such as difficulty of application and reported adverse effects (e.g., delayed cord detachment, sepsis, burns) further impeded use. Knowledge gaps and contrary instructions among and between both the HCWs and mothers also undermined CHX use. Conclusion Despite CHX being the recommended intervention for cord care in Kenya, its inconsistent use in Kiambu county reflects gaps in policy enforcement, supply chain reliability, and health education. The persistence of outdated or non-recommended cord care practices underscores a critical lack of oversight. To realize CHX's full public health potential, urgent policy action is needed to ensure consistent availability, enforcement of national neonatal guidelines, and investment into inclusive IEC materials. Bridging the gap between policy and practice is essential for reducing neonatal morbidity and achieving equitable progress towards Kenya's goal of Universal Health Coverage.